A few remarks on the establishment of local tax law in Poland - Rafał Dowgier (Prawo Budżetowe Państwa i Samorządu)
In the Polish tax system there are taxes that feed both the central budget and the budgets at the lowest level of territorial self-government, i.e. municipalities. The tax authority of communes is limited by the provisions of the Act, which means that it is the legislator who in fact decides on the shape of the local tax law. In the recent period, its activities have led to a significant reduction in the municipalities’ own income without compensation for the revenues lost by them. The study indicates the methods by which the legislator interferes in the tax revenues of communes. This phenomenon is all the more worrying as it is usually connected with the violation of generally accepted principles of good legislation.